Octopamine-like immunoreactivity in the brain and subesophageal ganglion of the honeybee - Kreißl, Sabine; Eichmüller, Stefan; Bicker, Gerd; Rapus, Jürgen; Eckert, Manfred (My University, 1994)
The organization of putative octopaminergic pathways in the brain and subesophageal ganglion of the honeybee was investigated with a well-defined polyclonal antiserum against octopamine. Five prominent groups of just over 100 immunoreactive (IR) somata were found in the cerebral ganglion: Neurosecretory cells in the pars intercerebralis innervating the corpora cardiaca via NCC I, one cluster mediodorsal to the antennal lobe, one scattered on both sides of the midline of the protocerebrum, one between the lateral protocerebral lobes and the dorsal lobes, and a single soma on either side of the central body. With the exception of the pedunculi and β-lobes of the mushroom bodies, varicose immunoreactive fibers penetrate all parts of the cerebral ganglion. Strong labelling was found in the central complex and the protocerebral bridge. Fine networks of labelled processes invade the antennal lobes, the calyces and a small part of the α-lobes of the mushroom bodies, the protocerebrum, and all three optic ganglia.
In the subesophageal ganglion, one labelled cell body was found in the lateral soma layer of the mandibular segment. Each of the three neuromeres contains a group of six to ten somata in the ventral median parts. Most of the ventral median cells send their neurites dorsally through the midline tracts, whereas the neurites of a few cells follow the ventral cell body neurite tracts.
Octopamine-IR was demonstrated in all neuropils that contain pathways for proboscis extension learning in honeybees. Because octopaminergic mechanisms seem to be involved in the behavioral plasticity of the proboscis extension reflex, our study provides anatomical data on the neurochemical organization of an appetitive learning paradigm.
Keywords: neurotransmitter; mushroom body; antennal lobe; ventral median cells; insect nervous system; 570